Action learning in postgraduate executive management education: an account of practice. (1st September 2016) - Ruane, Meadbh
ABSTRACT: The merits of action learning as a change tool and enabler of deep learning are well recognised. However, there is a gap in the literature of participants' stories regarding their experiences on accredited postgraduate executive programmes underpinned by an action learning philosophy. The following account of practice addresses this gap and recounts participant experiences, in their own words, combined with my insights into these learning experiences of a Master of Business Studies. While the programme is underpinned by an action learning philosophy, it does not discount programmed learning. However, programmed learning is not privileged over the executives' own experiences and knowledge of their own problems; they are seen as the experts. Throughout the programme, the participants are members of an action learning set in which they address real problems in their own organisations, problems on which they can take action. This account examines the experiences, as told by the executive participants, and so provides rich and in-depth insights into their learning experiences. It provides an opportunity for educators to appreciate the depth and richness of learning and change which can occur as a consequence of adopting an action learning approach on such programmes. Furthermore, this account provides evidence of how action learning can contribute and be an enabler to the development of executives as reflective and critical practitioners able to better face an ever more complex and challenging world.